2007
DOI: 10.1523/jneurosci.0601-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive Personality Predicts Dopamine-Dependent Changes in Frontostriatal Activity during Component Processes of Working Memory

Abstract: Dopaminergic drugs affect a variety of cognitive processes, but the direction and extent of effects vary across individuals and tasks.Paradoxical effects are observed, by which the same drug causes cognitive enhancing as well as adverse effects. Here, we demonstrate that individual differences in impulsive personality account for the contrasting effects of dopaminergic drugs on working memory and associated frontostriatal activity. We observed that the dopamine D 2 receptor agonist bromocriptine improved the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
225
7
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(265 citation statements)
references
References 58 publications
31
225
7
2
Order By: Relevance
“…Although this close functional relationship between SN/VTA integrity and CVLT performance was hypothesized it should be noted, that working memory span also seems to be influenced by integrity of the SN/VTA, hippocampus and frontal WM (as apparent from our multiple regression analyses). This is compatible with data indicating that dopaminergic neuromodulation is also related to memory span (Aalto, Bruck, Laine, Nagren, & Rinne, 2005;Cools, Sheridan, Jacobs, & D'Esposito, 2007). In our data, memory span was most strongly predicted by age and hippocampal MTR, and adding SN/VTA integrity explained 3% additional variance of working memory span performance.…”
Section: Discussionsupporting
confidence: 92%
“…Although this close functional relationship between SN/VTA integrity and CVLT performance was hypothesized it should be noted, that working memory span also seems to be influenced by integrity of the SN/VTA, hippocampus and frontal WM (as apparent from our multiple regression analyses). This is compatible with data indicating that dopaminergic neuromodulation is also related to memory span (Aalto, Bruck, Laine, Nagren, & Rinne, 2005;Cools, Sheridan, Jacobs, & D'Esposito, 2007). In our data, memory span was most strongly predicted by age and hippocampal MTR, and adding SN/VTA integrity explained 3% additional variance of working memory span performance.…”
Section: Discussionsupporting
confidence: 92%
“…It is noteworthy that DAT1 genotype is predictive of brain and behavioral responses to cognitive flexibility (GarciaGarcia et al, 2010) and, in particular, a recent study showed that DAT1 modulates striatal (caudate) activation as a function of working memory load in an updating task (Stollstorff et al, 2010). A role for striatal dopamine in cognitive flexibility and working memory updating is consistent with multiple behavioral pharmacological and imaging studies (Cools et al, 2007;Clatworthy et al, 2009;Frank and O'Reilly, 2006;Moustafa et al, 2008b). Thus, given the evidence that striatal activation predicts the extent to which cognitive training can be achieved with updating tasks (Dahlin et al, 2008a), future research should analyze the degree to which these training effects are modulated by variations with striatal dopaminergic genes such as DARPP-32, DAT1 and DRD2.…”
Section: Striatal Genetics Of Reinforcement and Decision Makingmentioning
confidence: 57%
“…Indeed, dopamine-releasing stimulants are well known to improve cognitive function in both participants with ADHD and healthy individuals (Klorman et al, 1984;Elliott et al, 1997). However, multiple studies have shown that whether dopaminergic agents (particularly D2 receptor agonists), improve or impair cognitive function strongly depends on baseline measures (Kimberg et al, 1998;Mehta et al, 2004;Roesch-Ely et al, 2005;Frank and O'Reilly, 2006;Cools et al, 2009Cools et al, , 2007Clatworthy et al, 2009). For example, D2 stimulation generally improves performance in individuals with low working memory span (Kimberg et al, 1998;Frank and O'Reilly, 2006), or high impulsivity (Cools et al, 2007), or low baseline DA synthesis (Cools et al, 2009), whereas it impairs performance in those in the opposite groups.…”
Section: Individual Differences In Response To Pharmacological Manipumentioning
confidence: 99%
“…This finding is also consistent with previous reports that the effects of other dopaminergic agents, such as the D 2 receptor agonist bromocriptine, depend on baseline impulsivity levels. In a working memory paradigm, Cools et al (2007) demonstrated that bromocriptine improved the updating of working memory in high-impulsive but not low-impulsive subjects. In keeping with that result, we find that tolcapone reduced impulsivity more in high-impulsive subjects.…”
Section: Discussionmentioning
confidence: 96%